Kayaking performance is altered in mentally fatigued young elite athletes - Staiano, W.; Bosio, A.; Piazza, G.; Romagnoli, M.; Invernizzi, P. L. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The present study aimed to assess the impact of 60 min of a cognitive demanding task inducing mental fatigue (Stroop) on kayaking performance in young elite athletes. The second objective was to elucidate the effect of mental fatigue on performance in a population of young under-17 elite athletes of national. METHODS: Thirteen under-17 elite kayakers completed 60 min of an incongruent Stroop color-word test, or the equivalent time in a control condition in a cross-over study design. Afterwards, participants completed a 2000 m kayaking time trial in which power output, stroke rate and time at the end of 400, 800, 1200, 1600 and 2000 m were recorded. Physiological and perceptual measures of heart rate (HR), blood lactate and rating of perceived exertion (RPE) were collected during the time trial. Psychological questionnaires were used to assess fatigue and mental demand of the Stroop. Subjective ratings of mental fatigue following the Stroop were almost certainly higher. RESULTS: Results of the time trial suggested that mental fatigue almost certainly impaired power output, stroke rate and time (552±30 s) compared to the control (521±36 s) condition. Yet, during the time trial RPE was almost certainly higher in the mental fatigue condition, while HR was reported to be possibly lower. Blood lactate resulted almost certainly lower in the mental fatigue state at completion of the time trial (10.3±1.5 vs. 12.2±1.6 mmol/L). CONCLUSIONS: Mental fatigue has an almost certain negative impact on 2000-m kayaking performance in young elite athletes.